ANALISIS FENOL TOTAL DAN UJI AKTIVITAS ANTIOKSIDAN DARI EKSTRAK BUAH SENTUL(Sandoricum koetjape Merr) - Bayani, Faizul (Hydrogen: Jurnal Kependidikan Kimia, 2016)
Sentul fruit (Sandoricum koetjape Merr.) is representing one kind of fruit that is amount enough abundance at West Nusa Tenggara, but it hasn’t been exploited in an optimal fashion and more castaway useless. Parts of sentul plant have been applied as traditional medicine. Sentul fruit can be oxidated by browning reaction when it is pared or sliced, these symptoms shown the existences of phenolic compounds so that very potential as antioxidant. To analyse total phenolic and antioxidant activity of methanol extract of sentul fruit, the Folin-Ciocalteu and DPPH methods have been used. Results of analysis for three treatment types of sampels ( A, B, and C) shown their total phenolic: 6,9 %, 12,86 %, and 9,36 % respectively and also their antioxidant activity shown by values of IC50 of eachs: 43,36 ppm (1/IC50 = 0,023 ppm-1); 40,53 ppm (1/IC50 = 0,025 ppm-1); and 44,43 ppm (1/IC50 = 0,0225 ppm-1) respectively. These results indicated that sentul fruit is very potensial as antioxidant.